An NMR microscopy study of water absorption in cork (Journal of Materials Science, 2000)
NMR Microscopy is used to measure the imbibition of water into natural cork, extractives-free cork and desuberised cork. The results clearly indicate that suberin is the key constituent which determines the ability of cork to resist water uptake. Furthermore, a particular suberin with distinct spectral properties as viewed by 13C NMR is shown to be the component responsible for cork resistance to water absorption. Laser confocal microscopy suggests that this function is associated with the role of suberin in preserving cell wall structure but the highly hydrophobic nature of suberin may also play an important role. The NMR microscopy study shows that the water absorbed by natural cork, after soaking for three days, is confined to the lenticels, narrow channels on the order of 1000 to 1500 μm in diameter. One incidental outcome is the observation of a clear down-field shift in NMR frequency for water near the cut transverse surfaces of the cork, an effect~associated with susceptibility inhomogeneity.

Spectral editing of 13C cp/MAS NMR spectra of complex systems: application to the structural characterisation of cork cell walls. (Solid state nuclear magnetic resonance, 2000)
A mathematical method of obtaining 13C CP/MAS subspectra of single components of a complex system is presented and applied to three- and four-component systems. The method is based on previously reported work that exploits different proton relaxation properties for different domains of an heterogeneous system. However, unlike the original method that obtained subspectra through a trial-and-error approach, the method here presented solves the problem mathematically, thus avoiding the time-consuming and non-rigorous trial-and-error step. The method is applied to mixtures of three and four polymers and to a more complex system: cork cell walls. As expected, as the number of components increases, the sharing of relaxation properties between different components is increasingly probable, either due to incidental coincidence of relaxation times or to specific interactions and intimate mixing of compounds. While this hinders the calculation of the subspectra of single chemical components, it may provide useful information about inter-component interactions. This possibility was demonstrated by the application of this method to cork cell walls. Both three-component and four-component approaches showed that three domains exist in cork cell walls: carbohydrate/lignin matrix, mobile suberin close to (probably bonded to) lignin groups (about 42% w/w) and hindered suberin close to (probably bonded to) carbohydrate-OCH2O groups (about 4% w/w).

Antimutagenicity of a suberin extract from Quercus suber cork. (Mutation research, 1999)
The possible protective effect of a suberin extract from Quercus suber cork on acridine orange (AO)-, ofloxacin- and UV radiation-induced mutagenicity (bleaching activity) in Euglena gracilis was examined. To our knowledge, the present results are the first attempt to analyse suberin in relation to mutagenicity of some chemicals. Suberin exhibits a significant dose-dependent protective effect against AO-induced mutagenicity and the concentration of 500 micrograms/ml completely eliminates the Euglena-bleaching activity of AO. The mutagenicity of ofloxacin is also significantly reduced in the presence of suberin (125, 250 and 500 micrograms/ml). However, the moderate protective effect of suberin on UV radiation-induced mutagenicity was observed only at concentrations 500 and 1000 micrograms/ml. Our data shows that suberin extract from Q. suber cork possess antimutagenic properties and can be included in the group of natural antimutagens acting in a desmutagenic manner.

Very high-resolution 1H MAS NMR of a natural polymeric material (Solid State Nuclear Magnetic Resonance, 1999)
The use of ultrafast magic angle spinning (>30 kHz) in tandem with delayed echo acquisition is shown to yield very high-resolution 1H MAS NMR spectra of complex natural organic materials. For the first time, very high-resolution 1H MAS NMR spectra are reported for cork and wood components, two natural materials with great economic importance. The effect of the spinning rate on the 1H NMR spectra was evaluated with single-pulse acquisition and delayed-echo acquisition. The delayed-echo acquisition spectra presented linewidths as sharp as 67 and 25 Hz. The narrow peaks, characterised by proton spin–spin and spin–lattice relaxation, were assigned to the isotropic chemical shifts and the general spectral features were shown to correlate with the sample chemical structure. The tentative assignments of cork 1H MAS NMR signals were presented.